Novel potential therapeutic targets of alopecia areata - Xu, Wen; Wan, Sheng; Xie, Bo; Song, Xiuzu (Frontiers in Immunology, 2023)
Alopecia areata (AA) is a non-scarring hair loss disorder caused by autoimmunity. The immune collapse of the hair follicle, where interferon-gamma (IFN-γ) and CD8+ T cells accumulate, is a key factor in AA. However, the exact functional mechanism remains unclear. Therefore, AA treatment has poor efficacy maintenance and high relapse rate after drug withdrawal. Recent studies show that immune-related cells and molecules affect AA. These cells communicate through autocrine and paracrine signals. Various cytokines, chemokines and growth factors mediate this crosstalk. In addition, adipose-derived stem cells (ADSCs), gut microbiota, hair follicle melanocytes, non-coding RNAs and specific regulatory factors have crucial roles in intercellular communication without a clear cause, suggesting potential new targets for AA therapy. This review discusses the latest research on the possible pathogenesis and therapeutic targets of AA.